Endovascular Recanalization for Acute Internal Carotid Artery Terminus Occlusion: A Subgroup Analysis From the Direct-MT Trial. Issue 4 (22nd October 2022) - Zhang, Yingying; Zhang, Lei; Zhang, Yongwei; Li, Zifu; Zhang, Yongxin; Xing, Pengfei; Chen, Wenhuo; Wang, Shouchun; Li, Tianxiao; Yang, Pengfei; Liu, Jianmin
Abstract : BACKGROUND: The efficacy of endovascular recanalization for internal carotid artery (ICA) terminus occlusion has not been completely evaluated. OBJECTIVE: To investigate the efficacy of endovascular recanalization for ICA terminus occlusion. METHODS: Data from Direct-MT, a randomized controlled trial, were applied. ICA terminus occlusions were diagnosed with preprocedure computed tomography angiography by the core laboratory. We dichotomized the ICA terminus occlusions into 2 groups (non-T and T) and analyzed the differences between them. Single-factor analysis and multiple logistic regression were applied to detect independent factors for clinical outcomes and futile recanalization. RESULTS: The rates of first-pass effect, successful recanalization, good clinical outcome, mortality, and futile recanalization were 22.3% (50 of 224), 83.0% (181 of 224), 24.6% (55 of 224), 26.7% (60 of 224), and 69.6% (126 of 181), respectively. Baseline National Institutes of Health Stroke Scale (negative factor; odds ratio [OR] 0.89; 95% CI 0.84-0.95; P < .001), hypertension (negative factor; OR 0.38; 95% CI 0.18-0.80; P = .010), Alberta Stroke Program Early CT Score ≥ 6 (OR 3.68; 95% CI 1.29-10.5; P = .014), tirofiban use (OR 2.46; 95% CI 1.16-5.19; P = .018), first-pass effect (OR 2.87; 95% CI 1.28-6.41; P = .010), and final extended thrombolysis in cerebral infarction ≥ 2b (OR, 3.50; 95% CI 1.17-10.4; P = .024) were independent factors for good clinical outcome. Baseline National Institutes of Health Stroke Scale (OR 1.12; 95% CI 1.05-1.20; P = .004), Alberta Stroke Program Early CT Score < 6 (OR 4.68; 95% CI 1.51-14.5; P = .007), tirofiban use (negative factor; OR 0.39; 95% CI 0.18-0.86; P = .020), and first-pass effect (negative factor; OR 0.44; 95% CI 0.19-0.99; P = .047) were independent factors for futile recanalization. CONCLUSION: More efforts in modifiable factors should be made to improve the efficacy of endovascular recanalization for better clinical outcomes and less futile recanalization in ICA terminus occlusions.